Bioremediation mechanisms of combined pollution of PAHs and heavy metals by bacteria and fungi: A mini review. (January 2017) - Liu, Shao-Heng; Zeng, Guang-Ming; Niu, Qiu-Ya; Liu, Yang; Zhou, Lu; Jiang, Lu-Hua; Tan, Xiao-fei; Xu, Piao; Zhang, Chen; Cheng, Min
Highlights: Species of bacteria and fungi that dealt with PAHs and heavy metals were reviewed. Factors affecting bioremediation of PAHs and heavy metals were discussed. Bioremediation mechanisms of PAHs and heavy metals were elucidated. Potential research needs for this field were discussed. Abstract: In recent years, knowledge in regard to bioremediation of combined pollution of polycyclic aromatic hydrocarbons (PAHs) and heavy metals by bacteria and fungi has been widely developed. This paper reviews the species of bacteria and fungi which can tackle with various types of PAHs and heavy metals entering into environment simultaneously or successively. Microbial activity, pollutants bioavailability and environmental factors (e.g. pH, temperature, low molecular weight organic acids and humic acids) can all affect the bioremediation of PAHs and heavy metals. Moreover, this paper summarizes the remediation mechanisms of PAHs and heavy metals by microbes via elucidating the interaction mechanisms of heavy metals with heavy metals, PAHs/PAHs metabolites with PAHs and PAHs with heavy metals. Based on the above reviews, this paper also discusses the potential research needs for this field.